Across the river : on the poetry of Mak Dizdar - Mahmutćehajić, Rusmir, 1948- (Abrahamic dialogues series., 2011)
The work of Mehmedalija GMakG Dizdar (1917G1971) is the cornerstone of modern Bosnian literature. His work blends influences from Bosnian Christian culture, Islamic mysticism, and the cultural remains of medieval Bosnia. The first part of this book focuses on DizdarGs collection Stone Sleeper. It argues that in his poetry Dizdar turns to spiritual resources suppressed during the time of communism, though few have been able fully to understand the traditional content of his post-traditional form. Rusmir MahmutcGÿehajicGÿ introduces readers to this traditional substance in the context of what he.